Potensi Penerapan Infrastruktur Hijau Permukaan Berpori (Permeable Pavement) dalam Mengurangi Genangan dan Banjir di Kacematan Panakukkang - Asyer Riansa; Muhammad Yamin Jinca; Venny Veronica Natalia (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2022)
Makassar City, which is the largest city in Eastern Indonesia, still often faces inundation and flooding. In some areas in Makassar City, inundation often occurs, one of which is in Panakukkang District. So it is necessary to pay attention to infrastructure that is environmentally friendly and does not interfere with the natural cycle of the environment. The purpose of this study is to identify the level of flood susceptibility, calculate the volume of surface runoff and the influence of the physical spatial aspects of the area, and identify the potential for the application of permeable pavement based on the physical and spatial aspects of the area. This research was conducted from February to May 2022 (3 months). This study uses data types in the form of rainfall, land elevation, land use, slope, soil type, road network, land use, and utilities. The analytical methods used are scoring, overlay, and hydrological analysis. The results obtained for most of the research area are in flood-prone areas of 816 hectares. The volume of runoff water is 13 m3/second/km2. Permeable pavement can be applied to a number of roads with an area of ​​0.86 km2 and is capable of absorbing a runoff volume of 2,526 m3/hour/km2.